2016
DOI: 10.1002/bit.25976
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for producing astaxanthin from the unicellular green alga Haematococcus pluvialis

Abstract: The unicellular green alga Haematococcus pluvialis has been exploited as a cell factory to produce the high‐value antioxidant astaxanthin for over two decades, due to its superior ability to synthesize astaxanthin under adverse culture conditions. However, slow vegetative growth under favorable culture conditions and cell deterioration or death under stress conditions (e.g., high light, nitrogen starvation) has limited the astaxanthin production. In this study, a new paradigm that integrated heterotrophic cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 41 publications
3
28
0
4
Order By: Relevance
“…2A, glycerol and sodium acetate had a slight but of no worth promotion on T. minus growth, and sucrose could barely offer any biomass accumulation, as well as xylose, galactose, mannose, L-rhamnose, maltose and starch investigated in this study but not shown here. Zhang et al (2016) reported that sodium acetate could be utilized as organic carbon source for Haematococcus pluvialis heterotrophy. Sucrose is another optional organic carbon substrate for microalgae heterotrophy, but it needs to be hydrolyzed prior to use (Wang et al, 2016c).…”
Section: Screening Of Organic Carbon Source and Nitrogen Sourcementioning
confidence: 99%
“…2A, glycerol and sodium acetate had a slight but of no worth promotion on T. minus growth, and sucrose could barely offer any biomass accumulation, as well as xylose, galactose, mannose, L-rhamnose, maltose and starch investigated in this study but not shown here. Zhang et al (2016) reported that sodium acetate could be utilized as organic carbon source for Haematococcus pluvialis heterotrophy. Sucrose is another optional organic carbon substrate for microalgae heterotrophy, but it needs to be hydrolyzed prior to use (Wang et al, 2016c).…”
Section: Screening Of Organic Carbon Source and Nitrogen Sourcementioning
confidence: 99%
“…Astaxanthin has been implicated in numerous health benefits in humans, including reduction in cardiovascular diseases, enhancement of the immune response and reduction in the occurrence of various cancers. (Ames 2018, Zhang and Wang 2015, Zhang et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This outcome revealed that the supply of CO 2 at 5% in basal medium stabilized the pH value throughout the culture period. As previously stated, pH was strongly dependent on the buffer capacity of the media [3,18,[22][23][24]. A lower concentration of CO 2 at 0.04% (air), 1% and 2.5% was insufficient, and the pH of the medium became more alkaline over time.…”
Section: Effects Of Co 2 Concentrationmentioning
confidence: 92%